2013
DOI: 10.1590/s1807-55092013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do "feedback" autocontrolado na aprendizagem do lançamento da bola da ginástica rítmica

Abstract: ResumoO objetivo do presente estudo foi investigar os efeitos da frequência autocontrolada de "feedback" na aprendizagem do lançamento da bola da ginástica rítmica. A amostra foi constituída de 24 crianças, de sete a 10 anos de idade, distribuídas em dois grupos em relação aos diferentes tipos de condições de "feedback": autocontrolado e externamente controlado. O estudo foi composto de uma fase de prática e um teste de retenção. Os resultados de um questionário revelaram que a maioria dos participantes do gru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…One of the main positive results of the intervention in the present study was the improvement in fine motor skills in EG that, despite being directly associated with academic performance, is little mentioned in literature when it comes to sports performance, but several sports require such skills [21][22][23] .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…One of the main positive results of the intervention in the present study was the improvement in fine motor skills in EG that, despite being directly associated with academic performance, is little mentioned in literature when it comes to sports performance, but several sports require such skills [21][22][23] .…”
Section: Discussionmentioning
confidence: 60%
“…Another study, which also used MDS, also found similar results, in which older schoolchildren (approximately 10 years of age) presented lower performance compared to younger ones 13 . Other studies with different methods also showed a decrease in motor performance and physical activity index as the age increased 21,22,23 .…”
Section: Discussionmentioning
confidence: 78%